2012
DOI: 10.1039/c2ay25450f
|View full text |Cite
|
Sign up to set email alerts
|

Interlaboratory validation of an environmental monitoring method for trace analysis of endocrine disrupting compounds

Abstract: O PDF relativo ao artigo que solicita, não se encontra disponível em Acesso Aberto. Motivos: O editor não permite o depósito e disponibilização em acesso aberto do PDF que solicita. Para consultar o documento deve aceder ao endereço do editor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In 2011, the European Union banned the use of bisphenol-A (BPA) for the production of polycarbonate (PC) baby bottles (European Union 2011a) due to the wide variety of possible toxic effects of this substance (Vandenberg et al 2012;Singh & Li 2012;Yang et al 2013;Vandenberg et al 2013;Mansilha et al 2013). Since then, a wide variety of alternative materials has entered the market.…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, the European Union banned the use of bisphenol-A (BPA) for the production of polycarbonate (PC) baby bottles (European Union 2011a) due to the wide variety of possible toxic effects of this substance (Vandenberg et al 2012;Singh & Li 2012;Yang et al 2013;Vandenberg et al 2013;Mansilha et al 2013). Since then, a wide variety of alternative materials has entered the market.…”
Section: Introductionmentioning
confidence: 99%
“…Media and amplitude control charts of BPA-d 16 , used for process evaluation through recovery studies, showed no relevant tendency, so no procedural review was necessary (Mansilha et al 2012). Table 3 summarizes the results of the high temperature migration tests showing, unequivocally, that BPA migration from PC containers is higher when compared to other plastic materials.…”
Section: Analytical Methods Validationmentioning
confidence: 99%
“…After elution, the extracts were evaporated to dryness, reconstituted within ethyl acetate, and derivatized using MSTFA (Mansilha et al 2012;Viñas et al 2010).…”
Section: Migration Studiesmentioning
confidence: 99%
See 2 more Smart Citations